Sani's Fortis See-Saw and initial devoicing - Ostapirat, Weera (2024)
Sani, like many other Loloish languages, has moved towards the weakening of all final stops into -7, which is further realized in modern dialects as abruptness of tone or constriction of the preceding vowel. One striking fact is that such end-constriction has lost its trace in syllables with *voiceless initials and has usually been found only in those with early *voiced initials or prefixes (except the nasal prefix).